Ruthenium oxide: a near 0.8 µm epsilon-near-zero medium for multipurpose nonlinear photonics - Wang, Lin; Yan, Jiahe; Yuan, Jiaqi; Lau, Kuen Yao; Dong, Junhao; Zheng, Jingying; Xu, Beibei; Yusoff, Norita Mohd; Mahdi, Mohd Adzir; Qiao, Yanbo; Zhang, Zuxing; Qiu, Jianrong; et al. (John Wiley and Sons Inc, 2025)
The intriguing optical response associated with the vanishingly small dielectric primitivity in epsilon-near-zero (ENZ) materials has offered unprecedented opportunities for photonics. Due to the high-limit of doping concentration, current homogeneous ENZ materials based on heavily doped conductive oxide including ITO usually exhibit a zero-permittivity wavelength (λ0) longer than 1200 nm. Here, this is identified with combined theoretical and experimental investigations that stoichiometric rutile-type RuO2 (r-RuO2) exhibits the shortest λ0 of near 800 nm among conductive oxides, benefiting from the high free electron concentration with characteristic Drude-type response. The ENZ effect is manifested by the strong field enhancement and the large nonlinear optical (NLO) response in colloidal processed r-RuO2 nanoparticles (NPs) and thin films. By ultrafast transient spectroscopy, the strong NLO response in r-RuO2 NPs is revealed to be the result of rapid thermalization/cooling of free electrons in the strong hybridized Ru-4d/O-2p orbitals. The ultrafast optical nonlinearity is exploited further for the development of multi-purpose all-optical switches that enable stable pulse laser generation in four mode-locked and Q-switched fiber lasers. Our results underscore the potential of stoichiometric metallic metal oxides as alternative ENZ materials for nonlinear photonics applications in the visible and NIR regions.